2023
DOI: 10.1186/s12967-023-04573-x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of machine learning to identify diagnostic genes in leukocytes for acute myocardial infarction patients

Lin Zhang,
Yue Liu,
Kaiyue Wang
et al.

Abstract: Background Acute myocardial infarction (AMI) has two clinical characteristics: high missed diagnosis and dysfunction of leukocytes. Transcriptional RNA on leukocytes is closely related to the course evolution of AMI patients. We hypothesized that transcriptional RNA in leukocytes might provide potential diagnostic value for AMI. Integration machine learning (IML) was first used to explore AMI discrimination genes. The following clinical study was performed to validate the results. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Support vector machine (SVM). The SVM [ 9 ] is another commonly employed algorithm in disease diagnosis [ 42 , 43 , 44 ]. The SVM, introduced by Vapnik in 1990, operates on labeled data.…”
Section: Multi-modal and Ai Used In Disease Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Support vector machine (SVM). The SVM [ 9 ] is another commonly employed algorithm in disease diagnosis [ 42 , 43 , 44 ]. The SVM, introduced by Vapnik in 1990, operates on labeled data.…”
Section: Multi-modal and Ai Used In Disease Diagnosismentioning
confidence: 99%
“…They used data from the GEO dataset GSE113079, achieving an AUC of 97.1% in the training set and 98.9% in the testing set. Zhang et al [ 44 ] introduced the Integration Machine Learning (IML) algorithm, incorporating a SVM, neural network (NN), RF, gradient boosting machine (GBM), decision trees (DT), and LASSO. This algorithm was applied to classify patients with Acute Myocardial Infarction (AMI) and stable coronary artery disease (SCAD), using GEO datasets GSE60993, GSE62646, GSE48060, and GSE59867, achieving an AUC over 90%.…”
Section: Reported Workmentioning
confidence: 99%
“…SVM has demonstrated its capability when it delivered a better performance than ANN [14]. SVM has been widely applied in various fields such as health [15]- [16], agriculture [17]- [18], geology [19], and etc. In machining field, SVM has been extensively applied in various studies for the prediction of machining performances in conventional and non-conventional machining.…”
Section: B Proposed Prediction Modelmentioning
confidence: 99%
“…studies indicated that changes in the levels of miRNAs in the valve itself do not necessarily correlate with an alteration of their levels in the plasma. 13 Therefore, circulating miRNAs might affect mainly myocardial remodeling or other systemic dysfunction but not local pathological valvular changes. Some studies have compared the levels of circulating miRNAs in patients with AVS with those in healthy control subjects to identify potential biomarkers and therapeutic targets.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Among these circulating miRNAs, some show similar expression patterns at the myocardial level, supporting the idea of a role in the myocardium. [13][14][15] Circulating miRNAs are often encapsulated in extracellular vesicles (EVs), which are small membrane-bound vesicles secreted by cells into the extracellular space. EVs can be classified into 3 primary subtypes: exosomes, large EVs (also known as microvesicles), and apoptotic bodies.…”
Section: Clinical Perspectivementioning
confidence: 99%